2008
DOI: 10.1152/ajpendo.00738.2007
|View full text |Cite
|
Sign up to set email alerts
|

Bax signaling regulates palmitate-mediated apoptosis in C2C12myotubes

Abstract: Insulin resistance is a primary characteristic of type 2 diabetes. Several lines of evidence suggest that accumulation of free fatty acids in skeletal muscle may at least in part contribute to insulin resistance and may be linked to mitochondrial dysfunction, leading to apoptosis. Palmitate treatment of several cell lines in vitro results in apoptosis and inhibits protein kinase B (Akt) activity in response to insulin. However, the role of Bax and Bcl-2 in regulating palmitate-induced apoptosis has not been we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
9
24
0
Order By: Relevance
“…An oxidative endpoint marker of DNA, 8-oxo-guanine has attracted particular attention since it is mutagenic it causes G-to-T transversions upon replication and has been suggested to play an important role in carcinogenesis [38]. In the current study, 2-DCB enhanced intracellular ROS generation in a time-dependent manner and the pretreatment of cells with NAC significantly prevented 2-DCB-induced apoptosis, indicating that Two major pathways, the extrinsic and intrinsic pathways, leading to caspase activation have been found [10,15]. Our data showed the activation of Fas and caspase-8 after the treatment with 2-DCB and PA.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…An oxidative endpoint marker of DNA, 8-oxo-guanine has attracted particular attention since it is mutagenic it causes G-to-T transversions upon replication and has been suggested to play an important role in carcinogenesis [38]. In the current study, 2-DCB enhanced intracellular ROS generation in a time-dependent manner and the pretreatment of cells with NAC significantly prevented 2-DCB-induced apoptosis, indicating that Two major pathways, the extrinsic and intrinsic pathways, leading to caspase activation have been found [10,15]. Our data showed the activation of Fas and caspase-8 after the treatment with 2-DCB and PA.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, Bid was cleaved by 2-DCB and PA. Bid can be cleaved by caspase-8, and the cleaved Bid as the carboxyl-terminal fragment translocates to the mitochondria to induce the release of cytochrome c [4]. Cytochrome c functions with Apaf-1 to induce caspase-9 activation, thereby initiating the apoptotic caspase cascade [15]. These two apoptotic pathways may be interconnected by the caspase-8-mediated cleavage of Bid, which triggers the activation of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant was collected as the cytosolic fraction and total cellular protein was obtained separately. Nuclear protein was extracted as described (Peterson et al, 2008). Briefly, cells were harvested in hypotonic buffer containing 50 mM NaCl and the nuclear pellet was collected, washed and subsequently lysed in buffer containing 500 mM NaCl.…”
Section: Wnt Signaling Activity Assaysmentioning
confidence: 99%
“…5 In vitro studies have demonstrated that exposure of myotubes to a high-fat (HF) environment results in increased caspase-3 activity 6 and DNA fragmentation. [7][8][9] Similarly, MCK(m)-hLPL mice (which accumulate muscle lipids) have a higher percentage of apoptotic nuclei in muscle, 5 while triacylglycerol infusion into lean mice increases muscle caspase-3 activation. 10 Additionally, 16 weeks of HF feeding has been shown to increase caspase-3 activity in mouse muscle.…”
Section: Introductionmentioning
confidence: 99%